The mediating effect of quality of life between family support and advance care planning readiness of older adult patients with chronic diseases - Lyu, Yongli; Liu, Yafang; Liu, Yuechen; Yang, Xinlian; Guo, Kai (Frontiers in Public Health, 2025)
ObjectiveTo investigate the mediating effect of quality of life (QoL) between family support and advance care planning (ACP) readiness among older adult patients with chronic diseases, thereby providing evidence for nursing administrators to strengthen family support and promote ACP preparedness.MethodsFrom November 2024 to February 2025, a total of 262 older adult patients with chronic diseases were recruited via convenience sampling from seven tertiary hospitals located in Guangdong, Hainan, Sichuan, Heilongjiang, and Hubei provinces. Data were collected using a general information questionnaire, the EuroQoL-5 Dimension (EQ-5D-5L) scale, the Family Support Scale, and the Advance Care Planning Readiness Scale.ResultsThe median EQ-5D-5L utility score was 0.831 (IQR: 0.640–0.942), the family support score was 12.00 (IQR: 12.00–13.00), and the mean ACP readiness score was 81.97 ± 9.88. Family support was found to be positively correlated with ACP readiness (r = 0.515, p < 0.01). Similarly, quality of life was also positively associated with ACP readiness (r = 0.552, p < 0.01). Furthermore, family support exhibited positive correlation with quality of life (r = 0.403, p < 0.01). Mediation analysis indicated that quality of life partially mediated the interrelationship between family support and ACP readiness, accounting for 25.5% of the total effect.ConclusionQuality of life plays a mediating role between family support and ACP readiness in older adult patients with chronic diseases. Nursing administrators should prioritize improving quality of life and fostering supportive family environments to enhance ACP preparedness.